Characterization of the probiotic properties of Lacticaseibacillus rhamnosus LR6 isolated from the vaginas of healthy Korean women against vaginal pathogens - Chung, Yusook; Kang, Seung Beom; Son, Dooheon; Lee, Ji Young; Chung, Myung Jun; Lim, Sanghyun (Frontiers in Microbiology, 2023)
The human microbiome exhibits intricate populations across the body, with the vaginal tract serving as an ecosystem characterized by the prevalence of the genus Lactobacillus. Disruptions in the vaginal microbiota, which are frequently linked to variables such as sexual activity, hormonal fluctuations, and excessive use of antibiotics, can result in vaginal dysbiosis and the development of diseases such as bacterial vaginosis (BV) and candidiasis. Lactobacillus species, owing to their capacity to create an acidic environment through the production of lactic acid, have a key function within this complex microbial community: they inhibit the growth of harmful microorganisms. This study aimed to investigate the genomic characteristics of L. rhamnosus LR6, a newly discovered strain isolated from the vaginal microbiota of 20 healthy women to assess its potential as a vaginal probiotic. We performed a comparative investigation of the genetic traits of L. rhamnosus using 45 publicly available genomes from various sources. We evaluated the genetic characteristics related to carbohydrate utilization, adhesion to host cells, and the presence of bacteriocin clusters. A comprehensive study was conducted by integrating in silico evaluations with experimental techniques to authenticate the physiological characteristics of strain LR6. We further used a rat model to assess the impact of L. rhamnosus LR6 administration on the changes in the gastrointestinal tract and the vaginal microbiome. The assessments revealed a significantly high inhibitory activity against pathogens, enhanced adherence to host cells, and high lactic acid production. Rat experiments revealed changes in both the fecal and vaginal microbiota; in treated rats, Firmicutes increased in both; Lactobacillaceae increased in the fecal samples; and Enterobacteriaceae decreased but Enterococcaceae, Streptococcaceae, and Morganellaceae increased in the vaginal samples. The study results provide evidence of the genetic characteristics and probiotic properties of LR6, and suggest that oral administration of L. rhamnosus LR6 can alter both gut and vaginal microbiome. Collectively, these findings establish L. rhamnosus LR6 as a highly promising candidate for improving vaginal health.